Biaya Operasi dan Subsidi Pemerintah Terhadap Penerbangan Perintis di Klimantan Timur - Ataline Muliasari (WARTA ARDHIA, 2009)
The research of operating cost and government subsidy side of pioneer flying has been it is found out that the operational cost of plane in one route is Rp. 12.000.000, so be needed government subsidy, because subsidy beremove the passanger get the normally ticket 195.000 become Rp. 1.460.000.